Geothermal study to explain man-made permafrost in tailings with raised surface - Knutsson, Roger; Viklander, Peter; Knutsson, Sven; Laue, Jan (Environmental Earth Sciences, 2018)
Deposition of mine tailings in a cold climate requires precautions as temporary sub-zero temperatures can imply considerable consequences to the storage due to creation of permafrost. The risk of creating man-made permafrost lenses due to tailings deposition exists even in regions with no natural permafrost, as material being frozen during winter might not fully thaw by the following summer. When such frozen layers thaw during later longer warmer periods, excess pore water pressure and large settlements might develop. Such implications close to the dam structure have to be avoided and therefore the risk of generating permafrost should be reduced. This paper describes a geothermal model for one-dimensional heat conduction analysis. The model is able to simulate the temperature profile in tailings where the surface elevation is constantly increased due to deposition. At the tailings surface, the boundary condition is the air temperature changing over time during the year. Air temperatures, tailings deposition schedule and tailings properties are given as input to the model and can easily be changed and applied to specific facilities. The model can be used for tailings facilities in cold regions, where the effects of tailings deposition on the temperature regime are of interest. Findings can improve tailings management by explaining man-made permafrost generation. The model can also aid in setting up appropriate deposition schedules and to prevent generation of permafrost layers. Validerad;2018;Nivå 2;2018-04-09 (andbra)